Three new species of Tubificinae, Oligochaeta, from two plateau lakes in Southwest China - Cui, Yongde; Wang, Hongzhu (Zootaxa, 2009)
Three new species of Tubificinae (Naididae, Oligochaeta), Varichaetadrilus vestibulatus n. sp., Aulodrilus apeniatus n. sp., and Ilyodrilus mesoprostatus n. sp., are reported from Fuxian Lake and Xingyun Lake of Yunnan Province, Southwest China. V. vestibulatus differs from its allies by possessing modified spermathecal chaetae and thinner cylindrical penial sheaths. A. apeniatus is unique in the genus by having no penis. I. mesoprostatus is distinguishable from congeners by its prostate glands joining middle portion of atria and having concave, cone-shaped cuticular penial sheaths. Twenty-eight species of freshwater oligochaetes have hitherto been recorded from Yunnan Province, including five endemic species from three plateau lakes.